Improving Management Strategies In Educational Institutions - Shokhista Akhunova; Nigorakhon Tillayeva (Periodica Journal, 2022)
Organization of pedagogical processes in the continuing education system on a scientific basis, ensuring the activity of subjects in achieving the set goals and ensuring efficiency, organizing innovative activities based on the coordination, control and objective evaluation of the school's activities and ensuring its effectiveness. The essence of the teacher's activity in the field is expressed in the implementation of information-analysis, goal-motivation, foresightplanning, organizational-executive, regulation-coordination, control-diagnostic functions. In the article, improving management strategies in educational institutions, increasing the effectiveness of the pedagogical process, the interaction of innovations in pedagogical processes
Keywords: pedagogical process